Financial and Economic Consequences of Distribution of Artificial Intelligence as a General-Purpose Technology - V. E. Rasskazov (Финансы: теория и практика)
The relevance of the article is due to increasing attention of the state and corporations to artificial intelligence technologies, developing strategies and increasing investments in technology. The aim of this article is to study artificial intelligence as a general-purpose technology, its distribution features and approaches to assessing and modelling the impact on production, organization finances and the economy. The study employed the methods of an AI qualitative analysis according to the classification of general-purpose technologies and a regression analysis of company production factors. The author analysed the data of 21 public Russian companies in the industry of hydrocarbon production, mining and metal production for 2014–2018. He proposed a model to assess the impact of AI technology on production, organization finances and the economy. The correlation analysis proved that capital expenditures and the market value of companies have a close relationship. The study revealed low productivity of assets of Russian companies. The investor expects to receive 28 kopecks for each rouble invested in the company’s assets, whereas foreign markets show a one to one ratio. The study highlighted the cyclicality of the performance of the company factors. The research did not expose general-purpose technology signals in the given time interval. The author concluded that under a quality classification, artificial intelligence is a general-purpose technology; however, at this stage, it is impossible to empirically observe the economic effect of the technology distribution. The proposed model may be of further use to study the effect of artificial intelligence on the finances of a company and the economy. The potential consequences of market monopolization due to the distribution of AI technologies allow for an argument for the state regulation of the technology adaptation process by business.